Comparison of Therapeutic Lipid Target Achievements Among High-Risk Patients in Oman. (May 2014) - Al-Waili, Khalid; Al-Zakwani, Ibrahim; Al-Dughaishi, Tamima; Baneerje, Yajnavalka; Al-Sabti, Hilal; Al-Hashmi, Khamis; Farhan, Hatem; Habsi, Khadija Al; Al-Hinai, Ali T.; Al-Rasadi, Khalid
We compared therapeutic lipid target achievements among patients with diabetes or coronary heart disease (CHD) in Oman. A retrospective chart review of 94 patients was conducted at an outpatient clinic in Sultan Qaboos University Hospital, Muscat, Oman. The variables included low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and apolipoprotein B (apo B). The overall mean age of the cohort was 59 ± 12 years, 54% were male, 66% were diabetic, 48% hypertensive, 45% had CHD, 94% were on simvastatin, 4% were on fenofibrate, and 2% were on both simvastatin and fenofibrate. Lipid goal attainments of calculated LDL-C (<2.6 mmol/L), apo B (<0.9 g/L), and non-HDL-C (<3.36 mmol/L) were reached in 52%, 39%, and 53% of the patients, respectively. A significant proportion of high-risk patients treated with lipid-lowering agents reach LDL-C but not the apo B treatment targets, suggesting that the use of apo B target values should also be considered.